Pengembangan Soal Matematika Berbasis Higher Order Thinking Skills (Hots) Integrasi Kebangsaan pada Siswa - Iin Tri Sasmita Sari; Adisel Adisel; Fatrima Santri Syafri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research is so that the next generation has a balanced knowledge between general knowledge and knowledge of national values. This research uses research and development (R&D). The data used in this study is sourced from validation sheets, validation sheets are used to obtain data about the validation results of experts on HOTS-based math problems. The problem was developed using plomp model consisting of four stages, namely preliminary investigation phase, design phase, realization/construkction phase, test stage, evaluation, and revision phase. In terms of validity, at the validation stage I, HOTS-based math problems are said to be invalid and not yet feasible to use. In phase II all suggestions of validators have been corrected and are said to be very valid and worth using. The material expert's assessment of the question obtained a percentage result of 84%, fall into the category is very valid. In conclusion, math problems based on higher order thinking skills (HOTS) national integration in students in grade VII even semesters are said to be feasible to use after being declared valid by the material expert. Keywords: HOTS, Character Education, Math Problems